On the calculation of rectangular plates by the variation method - Yessenbayeva, G.A.; Smailova, A.A. (Bulletin of the Karaganda University. Mathematics Series, 2016)
The article presents the calculation of rectangular plates by a variational method. For considered rectangular plate the research was conducted by the equilibrium conditions of the elementary strip isolated from the plate, by the method that was used in the works of V.Z.Vlasov. To illustrate the above variational method were given specific examples of the calculation of a square plate, hinged along the contour and loaded equally by distributed loading of given intensity, as well as a square plate, rigidly clamped along the contour. A comparative analysis of the results was carried out.